SPRINGATE S-SCORE MODEL TO PREDICT FINANCIAL DISTRESS , THE LAST STAGE TO CORPORATE BANKRUPTCY : A CASE STUDY OF PT.SEPATU BATA TBK. - Sazly, Syukron; Al Rasyid, Harun; Indah K, Agus Tri (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Financial distress is a condition that all company leaders and owners want to avoid, because this condition is a step towards bankruptcy. In this study, researchers used financial ratio data and S-Score values to examine the financial condition of PT Sepatu Bata Tbk from 2018 to 2023. The results show that the company's performance decreased significantly during that period, with financial problems starting in 2019 and continuing to worsen until in 2023. The increasing risk of bankruptcy is associated with a decrease in the value of financial ratios such as efficiency, leverage, liquidity and profitability, as well as a lower S-Score. Recommendations include reevaluating the financial approach, using better debt management, developing a financial recovery plan, working with financial experts, and improving financial performance oversight and oversight. By implementing these recommendations, companies are expected to improve their finances and reduce the risk of bankruptcy in the future.